Emergence of Resistance to Fluoroquinolones and Third-Generation Cephalosporins in Salmonella Typhi in Lahore, Pakistan - Farhan Rasheed; Muhammad Saeed; Nabil-Fareed Alikhan; David Baker; Mohsin Khurshid; Emma V. Ainsworth; A. Keith Turner; Ambereen Anwar Imran; Muhammad Hidayat Rasool; Muhammad Saqalein; Muhammad Atif Nisar; Muhammad Fayyaz ur Rehman; et al. (Microorganisms, 2020)
Extensively drug-resistant (XDR) Salmonella Typhi has been reported in Sindh province of Pakistan since 2016. The potential for further spread is of serious concern as remaining treatment options are severely limited. We report the phenotypic and genotypic characterization of 27 XDR S. Typhi isolated from patients attending Jinnah Hospital, Lahore, Pakistan. Isolates were identified by biochemical profiling; antimicrobial susceptibility was determined by a modified Kirby–Bauer method. These findings were confirmed using Illumina whole genome nucleotide sequence data. All sequences were compared to the outbreak strain from Southern Pakistan and typed using the S. Typhi genotyping scheme. All isolates were confirmed by a sequence analysis to harbor an IncY plasmid and the CTX-M-15 ceftriaxone resistance determinant. All isolates were of the same genotypic background as the outbreak strain from Sindh province. We report the first emergence of XDR S. Typhi in Punjab province of Pakistan confirmed by whole genome sequencing.